Wasatiyyah dan politik mensejahtera masa depan negara - Mohd Yusof Din, Dato' Hj; Engku Ahmad Zaki Engku Alwi, Profesor Madya Dr., 1968- (Institut Wasatiyyah Malaysia, 2015)
On wasatiyyah, a justice in Islamic governance in Malaysia.